Packaging development of dehydrated strawberry using quality function deployment for e-commerce - Mentari, S.; Ainuri, Machmudun; Falah, Muhammad Affan Fajar (IOP Publishing Ltd, 2022)
Dehydrated strawberry is product development from strawberry fresh fruit to improve, increase the shelf-life and value of the product. During the Covid-19 pandemic, shopping lifestyle has changed gradually into online buying through e-commerce that was growth significantly, it must be followed by producer to adapt and adopt the situation especially for purchasing decisions, while customers tend to choose products based on the packaging appearance. This study aimed to determine attributes of the packaging and technical needs for producer selling preparation of dehydrated strawberry in e-commerce based on customer needs. The method in this study that has proven effective in fulfilling customer needs is Quality Function Deployment (QFD) in product planning phase. QFD analysis begins with filtering Voice of Customer (VoC) using open questionnaire then at the stage of customer importance level and product performance using closed questionnaire, then compiled into attributes of customer needs. Technical requirements were brainstormed using discussion with local sellers on e-commerce. Two attributes with the highest priority to be realized is product information on the packaging is easy to read and understand and product-related information fully listed on the outer product packaging and the highest priority for the technical needs is addition of secondary packaging.